EVALUASI PENERAPAN MODEL PRAKTIK KEPERAWATAN PROFESIONAL (MPKP) DI RUMAH SAKIT UMUM DAERAH KRT SETJONEGORO WONOSOBO - styana Dewi, Erlinna; Al Ummah, M. Basirun Al Ummah; Iswati, Ning Iswati (LPPM STIKES MUHAMMADIYAH GOMBONG, 2013)
Professional Nursing Practice Model (MPKP) was developed with the aim to improve the quality of nursing care delivery at ward level to enable the provision of professional nursing care. The development of nursing care in the hospital is good in the knowledge and attitude but it is not indicated in their evaluation that shows the low quality of nursing services. KRT Setjonegoro General Hospital began to implement MPKP in Wonosobo since 2009 which aims to improve the quality of MPKP. The research was aimed to evaluate the MPKP practice in Edelweiss Room of Setjonegoro General Hospital including pre-and post-conference implementation, documentation of nursing process, nursing rounds, pass shift duty. The collection of data used a questionnaire containing questions about the pre and post conference, documentation of nursing process, nursing rounds, pass shift duty. This is an evaluation descriptive study (evaluation study). The populations were health officers who served in the Edeweis Room of KRT Setjonegoro Hospital Wonosobo and 15 respondents were taken as the samples by using total sampling technique. The variables were pre and post conference, nursing documentation, nursing rounds, pass shift duty. The results showed that the implementation of pre and post conference went well (100%), nursing documentation went well (100%), nursing Round reached 60%, pass shift duty reached 100%. Overall, the process of implementing MPKP in Edelweis Room of KRT Wonosobo General Hospital reached 100%. Keywords : Application, Evaluation, Professional Nursing Practice Model (MPKP)